(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Human resource development refers to initiatives that provide equal access to resources.Organizations need to invest in their development so that they may better serve the greater communityand environment of which they are a part. While planning for India’s human resources, both urban andrural growth was taken into account. The most difficult part is making progress in the rural. The goal ofrural development is to enhance the standard of living for those who live in rural communities. The goal isto help people in rural areas abandon their antiquated customs and embrace more modern ways of life.It’s been a major problem for the world’s economies, particularly those of less developed nations. Thereis a lot of strain on the social and economic fabric of many emerging Asian countries due to the growinggap in living standards between rural and urban regions. Because of these causes, rural development iscrucial. The growth of India as a whole depends critically on the success of its rural areas.